Synthesis and reactivity of magnetically diverse Au@ Ni core-shell nanostructures - Bharathan, Vysakh A.; Raj, Govind K.; Joy, Pattayil Alias; Vinod, Chathakudath P. (Particle & Particle Systems Characterization, 2014)
Core-shell bimetallic Au@Ni nanoparticles, with gold cores and thin nickel shells with overall size less than 10 nm, are synthesized and stabilized in pure cubic (fcc) and hexagonal (hcp) phase. Due to their unique crystal, electronic, and geometric structure, they show interesting magnetic and chemical properties. The Au@Ni-fcc is magnetic, whereas Au@Ni-hcp is non-magnetic. Both the bimetallic nanostructures are stable to surface oxidation until 150 degrees C and show excellent catalytic activity for p-nitrophenol reduction reaction.
Keywords: Au-Ni nanoparticles; bimetallic nanostructures; magnetic core-shell nanoparticles; oxidation resistance

Activity enhancement upon the incorporation of titanium: au@ti-sio2 core-shell nanocatalysts for the CO oxidation reaction - Sekhar, Anandakumari C. Sunil; Kottavarithottil Ziyad; Soni, Yogita; Vinod, Chathakudath P. (ChemCatChem, 2015)
The encapsulation of gold nanoparticles 8-12nm in size within a porous Ti-SiO2 shell to form a core-shell nanoarchitecture was investigated, and the catalytic activity of the resulting structure was probed. Detailed characterization of the synthesized materials shows that the core-shell morphology is lost beyond a certain amount of incorporated titanium, and results in normal gold-supported Ti-SiO2. The material has a high surface area (913m(2)g(-1)) and high porosity, both of which make it an excellent choice for catalytic applications. With the optimum amount of incorporated Ti, the core-shell catalyst shows excellent room-temperature CO oxidation activity over several cycles with retention of its morphology at higher temperatures.
Keywords: core-shell structures; gold nanoparticles; Oxidation; Ti-SiO2

Pd loaded amphiphilic COF as catalyst for multi-fold Heck reactions, C-C couplings and CO oxidation - Mullangi, Dinesh; Nandi, Shyamapada; Shalini, Sorout; Sreedhala, Sheshadri; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Scientific Reports, 2015)
COFs represent a class of polymers with designable crystalline structures capable of interacting with active metal nanoparticles to form excellent heterogeneous catalysts. Many valuable ligands/monomers employed in making coordination/organic polymers are prepared via Heck and C-C couplings. Here, we report an amphiphilic triazine COF and the facile single-step loading of Pd-0 nanoparticles into it. An 18-20% nano-Pd loading gives highly active composite working in open air at low concentrations (Conc. Pd(0) < 0.05 mol%, average TON 1500) catalyzing simultaneous multiple site Heck couplings and C-C couplings using `non-boronic acid' substrates, and exhibits good recyclability with no sign of catalyst leaching. As an oxidation catalyst, it shows 100% conversion of CO to CO2 at 150 degrees C with no loss of activity with time and between cycles. Both vapor sorptions and contact angle measurements confirm the amphiphilic character of the COF. DFT-TB studies showed the presence of Pd-triazine and Pd-Schiff bond interactions as being favorable.

Highly stable In-SBA-15 catalyst for vapor phase Beckmann rearrangement reaction - Kumar, Rawesh; Shah, Sneha; Bahadur, Jitendra; Melnichenko, Yuri B.; Sen, Debasis; Mazumder, S.; Vinod, Chathakudath P.; Chowdhury, Biswajit (Microporous and Mesoporous Materials, 2016)
The Indium doped SBA-15 material was prepared by sol-gel method and tested for vapor phase Beckman rearrangement reaction. Among three indium loading, In/Si ratio of 2/100 was found as an optimum composition in terms of caprolactam selectivity (100%) and cyclohexanone oxime conversion (100%). The catalysts were characterized by N-2 adsorption, small-angle X-rays/neutron scattering (SAXS/SANS), XRD, FESEM, HRTEM, EDX, UV, FTIR and NH3-TPD techniques. In-situ SANS experiment was performed on the adsorption of CO2 to detect the micropores in the mesopore wall. All catalysts samples have highly ordered hexagonal structure with well dispersed indium in the silica matrix. The fine tuning of weak and strong acid sites were found in indium doped SBA-15 (In/Si = 2/100) catalyst. The same catalyst showed optimum catalytic performance, high space time yield 114.4 mol/h/g(cat) and high stability till 6 h of reaction without deactivation. The micro-kinetic analysis showed that there were no external and internal diffusion limitations in the SBA-15 catalyst. The reaction mechanism of Beckmann rearrangement over In-SBA-15 has been elucidated. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: e-Caprolactam; In-situ SANS; indium; SAXS; SBA-15

Low band gap benzimidazole COF supported Ni3N as highly active OER catalyst - Nandi, Shyamapada; Singh, Santosh Kumar; Mullangi, Dinesh; Illathvalappil, Rajith; George, Leena; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2016)
Covalent organic frameworks (COFs) have structures and morphologies closely resembling graphenes, whose modular construction permits atomiclevel manipulations. This, combined with their porous structure, makes them excellent catalyst supports. Here, the high electrocatalytic activity of a composite, formed by supporting Ni3N nanoparticles on a benzimidazole COF, for oxygen evolution reaction is shown. The composite oxidizes alkaline water with a near-record low overpotential of 230 mV @ 10 mA cm(-2) (eta(10)). This high activity is attributed to the ability of the COF to confine the Ni3N nanoparticles to size regimes otherwise difficult to obtain and to its low band gap character (1.49 eV) arising from the synergy between the conducting Ni3N nanoparticles and the pi-conjugated COF. The COF itself, as a metalfree self-standing framework, has an oxygen evolution reaction activity with 10 of 400 mV. The periodic structure of the COF makes it serve as a matrix to disperse the catalytically active Ni3N nanoparticles favoring their high accessibility and thereby good charge-transport within the composite. This is evident from the amount of O-2 evolved (230 mmol h(-1) g(-1)), which, to the best of our knowledge, is the highest reported. The work reveals the emergence of COF as supports for electrocatalysts.

Simple, phosphine free, reusable Pd(II)-2,2 `-dihydroxybenzophenone-SBA-15 catalyst for arylation and hydrogenation reactions of alkenes - Lazar, Anish; Vinod, Chathakudath P.; Singh, Anand Pal (New Journal of Chemistry, 2016)
An efficient, simple, phosphine and co-catalyst free C-C coupling reaction heterogeneous catalyst via a post grafting method is developed and reported. A covalently anchored phosphine free Pd(II) based 2,2'-dihydroxybenzophenone (DHBP) complex over organofunctionalized SBA-15 has been synthesized by the reaction between aminofunctionalized SBA-15 (NH(2)SBA-15) and a 2,2'-dihydroxybenzophenone (DHBP) ligand, and further complexation with Pd(II)Cl-2 to get Pd(II)-DHBP@ SBA-15. The synthesized catalysts were characterized by elemental analysis, XRD, N-2 sorption analyses, TG, DTA, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. The synthesized catalysts were screened in arylation (Heck reactions) and hydrogenation reactions of alkenes, and the results show that Pd(II)-DHBP@ SBA-15 exhibits high conversion and selectivity towards arylation and hydrogenation reactions of alkenes with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity.

Synthesis of Au@Ni bimetallic core shell nanoparticle and nanochains in soyabean oil and their catalytic hydrogenation reactions - Bharathan, Vysakh A.; Yadukiran, V.; Lazar, Anish; Singh, Anand. P.; Vinod, Chathakudath P. (ChemistrySelect, 2016)
Synthesis of Au@Ni bimetallic core shell nanostructures using commercially available soya bean oil as the solvent through a sequential reduction strategy is reported. The energy efficiency and economic viability comes from the much milder temperatures and replacement of expensive and environmentally hazardous solvents like long chain organic amines and acids previously reported for synthesis. Thus, core shell nanoparticles having size regime of 10-15 nm with an excellent control over the nickel shell thickness (2 nm) over the gold core (8-10 nm) and Au@Ni nanochains is achieved. The synthesized materials are demonstrated to synergistically catalyze hydrogenation of nitro and C-C multiple bonds with much better efficiency as compared to individual nanoparticle counterparts.
Keywords: Bimetallic nanoparticles; Gold catalysis; hydrogenation reactions; synergistic effects

Highly stable COF-supported Co/Co(OH)(2) nanoparticles heterogeneous catalyst for reduction of nitrile/nitro compounds under mild conditions - Mullangi, Dinesh; Chakraborty, Debanjan; Pradeep, Anu; Koshti, Vijay; Vinod, Chathakudath P.; Panja, Soumendranath; Nair, Sunil; Vaidhyanathan, Ramanathan (Small, 2018)
Ordered nanoporosity in covalent organic framework (COF) offers excellent opportunity for property development. Loading nanoparticles (nPs) onto them is one approach to introducing tailor-made properties into a COF. Here, a COF-Co/Co(OH)(2) composite containing about 16 wt% of <6 nm sized Co/Co(OH)(2) nPs is prepared on a N-rich COF support that catalyzes the release of theoretical equivalence of H-2 from readily available, safe, and cheap NaBH4. Furthermore, the released H-2 is utilized for the hydrogenation of nitrile and nitro compounds to amines under ambient conditions in a facile one-pot reaction. The COF "by choice" is built from "methoxy" functionalized dialdehydes which is crucial in enabling the complete retention of the COF structure under the conditions of the catalysis, where the regular Schiff bonds would have hydrolyzed. The N-rich binding pockets in the COF ensure strong nP-COF interactions, which provides stability and enables catalyst recycling. Modeling studies reveal the crucial role played by the COF in exposing the active facets and thereby in controlling the activation of the reducing agent. Additionally, via density functional theory, we provide a rational explanation for how these COFs can stabilize nanoparticles which grow beyond the limiting pore size of the COF and yet result in a truly stable heterogeneous catalyst - a ubiquitous observation. The study underscores the versatility of COF as a heterogeneous support for developing cheap and highly active nonnoble metal catalysts.

Mesoporous shell@macroporous core aluminosilicates as sustainable nanocatalysts for direct N-alkylation of amines - Sekhar, Anandakumari C. Sunil; Ashokkumar, Anumol Erumpukuthickal; Cygnet, Choorapoikayil T.; Lakshmi, Saseendranpillai Vidhya; Deepak, Francis Leonard; Vinod, Chathakudath P. (Chemnanomat, 2018)
Aluminosilicate spheres with a macroporous core and mesoporous shell (Si/Al ratio of 11) is synthesised by a sol-gel method utilizing cetyltrimethyl ammonium bromide (CTAB) as a structure directing agent in basic medium. The selective incorporation of aluminium in the silica matrix results in the formation of aluminosilicates with an overall acidity of 0.32mmol/g with interconnected pores. Direct N-alkylation reaction is a prototype of C-N bond formation reaction and meso- macroporous aluminosilicate is shown to catalyze this reaction with excellent yield. The catalyst is tested and found sustainable for five catalytic cycles even without any high temperature regeneration step.
Keywords: Aluminosilicates; macroporous; Mesoporous; N-alkylation; nanocatalysis

Selective oxidation of cyclohexane to cyclohexanone using chromium oxide supported mesoporous MCM-41 nanospheres: probing the nature of catalytically active chromium sites - Betsy, Kurisingal J.; Nayak, Chandrani; Lazar, Anish; Krishnan, Athira; Bhattacharyya, Dibyendu; Jha, Shambhu N.; Vinod, Chathakudath P. (ChemCatChem, 2018)
Highly dispersed chromium oxide supported mesoporous MCM-41 nanosphere catalysts have been synthesized using a simple wet impregnation method. This work is devoted to a systematic study to reveal the active Cr sites in chromium oxide supported MCM-41 nanosphere catalysts for the selective oxidation of cyclohexane to cyclohexanone. To probe the nature of the active species, we synthesized 0.5-10wt% Cr loaded catalysts and characterized them by using XRD, UV/Vis spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, extended X-ray absorption fine structure analysis, X-ray absorption near edge structure analysis, N-2 sorption analysis, FTIR spectroscopy, (SiNMR)-Si-29 spectroscopy, SEM, and TEM. The liquid-phase oxidation of cyclohexane to cyclohexanone (99% selectivity) was performed under mild reaction conditions, and the results reveal clearly that the 5wt% Cr loaded catalyst was optimum for the reaction. The initial composition of isolated Cr3+ species in the catalyst is the major factor that influences the enhanced activity for cyclohexane oxidation.
Keywords: chromium; heterogeneous catalysis; Nanostructures; Oxidation; supported catalysts

Carbon derived from soft pyrolysis of a covalent organic framework as a support for small-sized RuO2 showing exceptionally low overpotential for oxygen evolution reaction - Chakraborty, Debanjan; Nandi, Shyamapada; Illathvalappil, Rajith; Mullangi, Dinesh; Maity, Rahul; Singh, Santosh K.; Haldar, Sattwick; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (ACS Omega, 2019)
Electrochemical water splitting is the most energy-efficient technique for producing hydrogen and oxygen, the two valuable gases. However, it is limited by the slow kinetics of the anodic oxygen evolution reaction (OER), which can be improved using catalysts. Covalent organic framework (COF)-derived porous carbon can serve as an excellent catalyst support. Here, we report high electrocatalytic activity of two composites, formed by supporting RuO2 on carbon derived from two COFs with closely related structures. These composites catalyze oxygen evolution from alkaline media with overpotentials as low as 210 and 217 mV at 10 mA/cm(2), respectively. The Tafel slopes of these catalysts (65 and 67 mV/dec) indicate fast kinetics compared to commercial RuO2. The observed activity is the highest among all RuO2-based heterogeneous OER catalysts-a touted benchmark OER catalyst. The high catalytic activity arises from the extremely small-sized (similar to 3-4 nm) RuO2 nanoparticles homogeneously dispersed in a micro-mesoporous (BET = 517 m(2)/g) COF-derived carbon. The porous graphenic carbon favors mass transfer, while its N-rich framework anchors the catalytic nanoparticles, making it highly stable and recyclable. Crucially, the soft pyrolysis of the COF enables the formation of porous carbon and simultaneous growth of small RuO2 particles without aggregation.

Cu/Cu2O nanoparticles supported on a phenol-pyridyl COF as a heterogeneous catalyst for the synthesis of unsymmetrical diynes via glaser-hay coupling - Chakraborty, Debanjan; Nandi, Shyamapada; Mullangi, Dinesh; Haldar, Sattwick; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (ACS Applied Materials & Interfaces, 2019)
Covalent organic frameworks (COFs) are a new class of porous crystalline polymers with a modular construct that favors fiinctionalization. COF pores can be used to grow nanoparticles (nPs) with dramatic size reduction, stabilize them as dispersions, and provide excellent nP access. Embedding substrate binding sites in COFs can generate host-guest synergy, leading to enhanced catalytic activity. In this report, Cu/Cu2O nPs (2-3 nm) are grown on a COF, which is built by linking a phenolic trialdehyde and a triamine through Schiff bonds. Their micropores restrict the nP to exceptionally small sizes (similar to 2-3 nm), and the pore walls decorated with strategically positioned hydrogen-bonding phenolic groups anchor the substrates via hydrogen-bonding, whereas the basic pyridyl sites serve as cationic species to stabilize the [CuclusterCl2](2-) type reactive intermediates. This composite catalyst shows high activity for Glaser-Hay heterocoupling reactions, an essential 1,3-diyne yielding reaction with widespread applicability in organic synthesis and material science. Despite their broad successes in homocoupled products, preparation of unsymmetrical 1,3-diynes is challenging due to poor selectivity. Here, our COF-based Cu catalyst shows elevated selectivity toward heterocoupling product(s) (Cu nP loading 0.0992 mol %; turn over frequency: similar to 4S-50; turn over number: similar to 17S-190). The reversible redox activity at the Cu centers has been demonstrated by carrying out X-ray photoelectron spectroscopy on the frozen reactions, whereas the crucial interactions between the substrates and the binding sites in their optimized configurations have been modeled using density functional theory methods. This report emphasizes the utility of COFs in developing a heterogeneous catalyst for a truly challenging organic heterocoupling reaction.
Keywords: Copper nanoparticles; Covalent organic framework; Glaser-Hay heterocoupling; heterogeneous catalysis; unsymmetrical diynes

MnO2@Fe3O4 Magnetic Nanoparticles as Efficient and Recyclable Heterogeneous Catalyst for Benzylic sp(3) C-H Oxidation - Pandey, Akanksha M.; Agalave, Sandip G.; Vinod, Chathakudath P.; Gnanaprakasam, Boopathy (Chemistry-An Asian Journal, 2019)
Herein, we report a highly chemoselective and efficient heterogeneous MnO2@Fe3O4 MNP catalyst for the oxidation of benzylic sp(3) C-H group of ethers using TBHP as a green oxidant to afford ester derivatives in high yield under batch/continuous flow module. This catalyst was also effective for the benzylic sp(3) C-H group of methylene derivatives to furnish the ketone in high yield which can be easily integrated into continuous flow condition for scale up. The catalyst is fully characterized by spectroscopic techniques and it was found that 0.424 % MnO2@Fe3O4 catalyzes the reaction; the magnetic nanoparticles of this catalyst could be easily recovered from the reaction mixture. The recovered catalyst was recycled for twelve cycles without any loss of the catalytic activity. The advantages of MnO2@Fe3O4 MNP are its catalytic activity, easy preparation, recovery, and recyclability, gram scale synthesis with a TOF of up to 14.93 h(-1) and low metal leaching during the reaction.

Boron nitride and oxide supported on dendritic fibrous nanosilica for catalytic oxidative dehydrogenation of propane - Belgamwar, Rajesh; Rankin, Andrew G. M.; Maity, Ayan; Mishra, Amit Kumar; Gomez, Jennifer S.; Trebosc, Julien; Vinod, Chathakudath P.; Lafon, Olivier; Polshettiwar, Vivek (ACS Sustainable Chemistry & Engineering, 2020)
In this work, we were able to significantly increase the activity of boron nitride (BN) catalysts used for the oxidative dehydrogenation (ODH) of propane by designing and synthesizing BN supported on dendritic fibrous nanosilica (DFNS). DFNS/BN showed a markedly increased catalytic efficiency, accompanied by exceptional stability and selectivity. Textural characterization, together with solid-state nuclear magnetic resonance (NMR) and X-ray photoelectron spectroscopic analyses, indicates the presence of a combination of unique fibrous morphology of DFNS and various boron sites connected to silica to be the reason for this increase in the catalytic performance. Notably, DFNS/B2O3 also showed catalytic activity, although with more moderate selectivity compared to that of DFNS/BN. Solid-state NMR spectra indicate that the higher selectivity of DFNS/BN might stem from a larger amount of hydrogen-bonded hydroxyl groups attached to B atoms. This study indicates that both boron nitride and oxide are active catalysts and by using high surface area support (DFNS), conversion from propane to propene as well as productivity of olefins was significantly increased.
Keywords: Electron microscopy; heterogeneous catalysis; Nanostructures; NMR spectroscopy; propane dehydrogenation; X-ray diffraction; X-ray photoelectron spectroscopy

Nanoporous covalent organic framework embedded with Fe/Fe3O4 nanoparticles as air-stable low-density nanomagnets - Kushwaha, Rinku; Kaleeswaran, Dhananjayan; Haldar, Sattwick; Chakraborty, Debanjan; Mullangi, Dinesh; Borah, Aditya; Vinod, Chathakudath P.; Murugavel, Ramaswamy; Vaidhyanathan, Ramanathan (ACS Applied Nano Materials, 2020)
Covalent organic frameworks (COFs) made of light atoms such as H, C, N, and O with a significant void-to-framework ratio are excellent low-density supports for nanoparticles (nPs). Their framework can be precoded with heteroatoms to ensure binding with metallic nanoclusters. With these advantages, if controlled amounts of magnetic nPs are anchored to them, they can yield low-density organic-inorganic nanomagnets. Their organic nature facilitates fusion with bulk materials such as paper/textile to enable bulk composites with well-dispersed low-density magnets, which have potential for defense and next-generation aviation applications. Herein, we have grown small Fe/Fe3O4 nPs (5-18 wt %) inside a COF. Interestingly, 300 mg of this organic-inorganic framework material (containing 50 mg of nPs) can lift a vial of similar to 15,000 mg (300 times heavier). Also, the hydrophobic COF wraps around the Fe/Fe3O4 nanocluster retaining its room-temperature magnetic character even after 1 year, while the naked nPs lose it within a few days because of air oxidation. Bulk composites with paper and polymers have been made using this low-density Fe-COF to demonstrate their processability.
Keywords: air-stable nanomagnets; Covalent organic framework; Fe/Fe3O4 nanoparticles; low-density nanomagnets; magnetic rayon; nanoporous COF

Can we identify the salt-cocrystal continuum state using XPS? - Tothadi, Srinu; Shaikh, Tabrez Rafique; Gupta, Sharad; Dandela, Rambabu; Vinod, Chathakudath P.; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
X-ray photoelectron spectroscopy (XPS) is used to understand the nature of acid-base crystalline solids, to know whether the product is a salt (proton transfer, O-center dot center dot center dot H-N+) or a cocrystal (neutral adduct, O-H center dot center dot center dot N). The present study was carried out to explore if intermediate states of proton transfer from COOH to nitrogen (the proton resides between hydrogen bonded to O and N, O center dot center dot center dot H center dot center dot center dot N, quasi state) can be differentiated from a salt (complete proton transfer, N+-H center dot center dot center dot center dot O-) and cocrystal (no proton transfer, O-H center dot center dot center dot N) using N 1s XPS spectroscopy. The intermediate states of proton transfer arise when the pK(a) difference between the acid and the conjugate base is between -1 and 4, -1 < Delta pK(a) < 4, a situation common with COOH and pyridine functional groups present in drug molecules and pharmaceutically acceptable coformers. Complexes of pyridine N bases with aromatic COOH molecules in nine salts/cocrystals were cocrystallized, and their N 1s core binding energies in XPS spectra were measured. The proton state was analyzed by single-crystal X-ray diffraction for confirmation. Three new complexes were crystallized and analyzed by XPS spectra (without knowledge of their X-ray structures), to assess the predictive ability of XPS spectra in differentiating salt-cocrystal intermediate states against the extremities. The XPS results were subsequently confirmed by single-crystal X-ray data. Complexes of 3,5-dinitrobenzoic acid and isonicotinamide in 1:1 and 1:2 ratios exist as a salt and a salt-cocrystal continuum, respectively, as shown by the N 1s core binding energies. The proton states of the crystalline solids by XPS are in good agreement with the corresponding crystal structures. Other complexes, such as those of 3,5-dinitrobenzoic acid with 1,2-bis(4-pyridyl)ethylene, exhibit a salt-cocrystal continuum, maleic acids with 1,2-bis(4-pyridyl)ethylene and acridine are salts, 2-hydroxybenzoic acid and acridine is a salt, and the complex of 3,5-dinitrobenzoic acid and 3-hydroxypyridine is a salt and salt-cocrystal continuum, while fumaric acids with 1,2-bis(4-pyridyl)ethylene and acridine are cocrystals. Furthermore, three new acidbase complexes of 3,5-dinitrobenzoic acid with phenazine, 4-hydroxypyridine, and 4-cyanopyridine were studied initially by XPS and then confirmed by X-ray diffraction. In summary, since the N 1s binding energies cluster in a narrow range as cocrystals (398.7-398.9 eV) and salts (400.1-401.1 eV), it is clearly possible to differentiate between cocrystals and salts, but the saltcocrystal continuum values in XPS spectra are clustered in an intermediate range of cocrystals and salts but overlap with those of cocrystal or salt binding energies.

Lithium silicate nanosheets with excellent capture capacity and kinetics with unprecedented stability for high-temperature CO2 capture - Belgamwar, Rajesh; Maity, Ayan; Das, Tisita; Chakraborty, Sudip; Vinod, Chathakudath P.; Polshettiwar, Vivek (Chemical Science, 2021)
An excessive amount of CO2 is the leading cause of climate change, and hence, its reduction in the Earth's atmosphere is critical to stop further degradation of the environment. Although a large body of work has been carried out for post-combustion low-temperature CO2 capture, there are very few high temperature pre-combustion CO2 capture processes. Lithium silicate (Li4SiO4), one of the best known high-temperature CO2 capture sorbents, has two main challenges, moderate capture kinetics and poor sorbent stability. In this work, we have designed and synthesized lithium silicate nanosheets (LSNs), which showed high CO2 capture capacity (35.3 wt% CO2 capture using 60% CO2 feed gas, close to the theoretical value) with ultra-fast kinetics and enhanced stability at 650 degrees C. Due to the nanosheet morphology of the LSNs, they provided a good external surface for CO2 adsorption at every Li-site, yielding excellent CO2 capture capacity. The nanosheet morphology of the LSNs allowed efficient CO2 diffusion to ensure reaction with the entire sheet as well as providing extremely fast CO2 capture kinetics (0.22 g g(-1) min(-1)). Conventional lithium silicates are known to rapidly lose their capture capacity and kinetics within the first few cycles due to thick carbonate shell formation and also due to the sintering of sorbent particles; however, the LSNs were stable for at least 200 cycles without any loss in their capture capacity or kinetics. The LSNs neither formed a carbonate shell nor underwent sintering, allowing efficient adsorption-desorption cycling. We also proposed a new mechanism, a mixed-phase model, to explain the unique CO2 capture behavior of the LSNs, using detailed (i) kinetics experiments for both adsorption and desorption steps, (ii) in situ diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy measurements, (iii) depth-profiling X-ray photoelectron spectroscopy (XPS) of the sorbent after CO2 capture and (iv) theoretical investigation through systematic electronic structure calculations within the framework of density functional theory (DFT) formalism.

Operando generated ordered heterogeneous catalyst for the selective conversion of CO2 to methanol - Cherevotan, Arjun; Raj, Jithu; Dheer, Lakshay; Roy, Soumyabrata; Sarkar, Shreya; Das, Risov; Vinod, Chathakudath P.; Xu, Shaojun; Wells, Peter; Waghmare, V, Umesh; Peter, Sebastian C. (ACS Energy Letters, 2021)
The discovery of new materials for efficient transformation of carbon dioxide (CO2) into desired fuel can revolutionize large-scale renewable energy storage and mitigate environmental damage due to carbon emissions. In this work, we discovered an operando generated stable Ni-In kinetic phase that selectively converts CO2 to methanol (CTM) at low pressure compared to the state-of-the-art materials. The catalytic nature of a well-known methanation catalyst, nickel, has been tuned with the introduction of inactive indium, which enhances the CTM process. The remarkable change in the mechanistic pathways toward methanol production has been mapped by operando diffuse reflectance infrared Fourier transform spectroscopy analysis, corroborated by first-principles calculations. The ordered arrangement and pronounced electronegativity difference between metals are attributed to the complete shift in mechanism. The approach and findings of this work provide a unique advance toward the next-generation catalyst discovery for going beyond the state-of-the-art in CO2 reduction technologies.

Coordination flexibility aided CO2-specific gating in an iron isonicotinate MOF - Singh, Himan Dev; Nandi, Shyamapada; Chakraborty, Debanjan; Singh, Kirandeep; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Chemistry-an Asian Journal, 2022)
Coordination flexibility assisted porosity has been introduced into an Iron-isonicotinate metal-organic framework (MOF), (Fe(4-PyC)(2) . (OH). The framework showed CO2-specific gate opening behavior, which gets tuned as a function of temperature and pressure. The MOF ` s physisorptive porosity towards CO2, CH4, and N-2 was investigated; it adsorbed only CO2 via a gate opening phenomenon. The isonicotinate, representing a borderline soft base, is bound to the hard Fe3+ centre through monodentate carboxylate and pyridyl nitrogen. This moderately weak binding enables isonicotinate to spin like a spindle under the CO2 pressure opening the gate for a sharp increase in CO2 uptake at 333 mmHg (At 298 K, the CO2 uptake increases from 0.70 to 1.57 mmol/g). We investigated the MOF ` s potential for CO2/N-2 and CO2/CH4 gas separation aided by this gating. IAST model reveals that the CO2/N-2 selectivity jumps from 325 to 3131 when the gate opens, while the CO2/CH4 selectivity increases three times. Interestingly, this Fe-isonicotinate MOF did not follow the trend set by our earlier reported Hard-Soft Gate Control (established for isostructural M2+-isonicotinate MOFs (M=Mg, Mn)). However, we account for this discrepancy using the different oxidation state of metals confirmed by X-ray photoelectron spectroscopy and magnetism.
Keywords: CO2 capture; flexible MOF; gating; Isonicotinic

Covalent organic framework with electrodeposited copper nanoparticles - a desirable catalyst for the Ullmann coupling reaction - Chandran, Chandana; Singh, Himan Dev; Leo, Liya S.; Shekhar, Pragalbh; Rase, Deepak; Chakraborty, Debanjan; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Journal of Materials Chemistry A, 2022)
A covalent organic framework is a porous covalently-linked polymeric assembly built from molecular lego blocks, the monomers. A COF's high surface area, ordered pores, and intrinsic low density makes it a perfect heterogeneous catalyst component. Dispersing catalytic metal nanoparticles into the porous COF matrix in a `capping-agent-free' manner can aid the maximal utilization of the active sites. To generate single-site catalysts, metals have been anchored to dense supports, or metal ions have been coordinated to the porous organic framework. The latter has superior atom efficiency and a substrate diffusion advantage. Stably nestling neutral metallic clusters into open-framework supports with no specifically strong binding groups requires a different approach. If infused from extremely dilute electrolytes, metal clusters can be nanoconfined into electrically activated COFs. At low-loadings, it can resemble a single-site catalyst with high atom efficiency. Herein, we report the larger scale synthesis of IISERP-COF15 and electrochemical loading of copper nanoparticles into its pores at loadings as low as 3.34 wt%. We employed classical Ullmann reactions to adjudge its activity. Typical turnover numbers for the catalysts reported in the literature are approximately 50-100. A Cu@COF shows high activity with a very low catalyst loading of 0.25 mol% (TON around similar to 300-350 vs. 4 for neat CuCl2 center dot 2H(2)O (homogeneous catalyst) and turnover frequency (similar to 15-17 h(-1))). We recycled it for up to 3 cycles. Furthermore, we report a multi-fold Ullmann reaction producing an unreported hexaaldehyde to demonstrate the latitude of the catalyst. Our work points to the potential of a dilutely loaded metal@COF as a mimic of the single-site catalyst for synthesizing valuable C-O linked molecules. Our findings from computational modeling shed light on the role of the COF as an active nanoporous support for Ullmann C-O coupling.

Green transformation of CO2 to ethanol using water and sunlight by the combined effect of naturally abundant red phosphorus and Bi2MoO6 - Das, Risov; Das, Kousik; Ray, Bitan; Vinod, Chathakudath P.; Peter, Sebastian C. (Energy & Environmental Science, 2022)
Direct photocatalytic conversion of CO2 to ethanol remains a scientific challenge because of the sluggish kinetics of C-C coupling and complex multielectron transfer processes. To achieve a green transformation of CO2 to C1+ products using naturally abundant sunlight and water requires the smart design of an efficient catalyst by selecting the right combination of atoms either in elemental or in compound form. Herein, we report a composite photocatalyst composed of earth abundant red phosphorus (RP) in nano-sheet morphology decorated with Bi2MoO6 nano-particles. The composite synthesised by a facile ultrasonication method produces 51.8 mu mol g(-1) h(-1) of ethanol from CO2. The ability of RP for the conversion of CO2 to C1 has been altered by the introduction of Bi2MoO6. In situ Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS) and Kinetic Isotopic Effect (KIE) analysis shed light on the mechanistic pathway, which propose that the presence of Bi-Mo dual sites play a crucial role in the C-C coupling toward the formation of ethanol. Spectroscopic evidence and isotope labeling experiments suggest that the intermediate OCH3* is the key active species for ethanol formation via self-coupling followed by proton transfer.

Improvement in oxygen evolution performance of NiFe layered double hydroxide grown in the presence of 1T-Rich MoS2 - Chakraborty, Soumita; Marappa, Shivanna; Agarwal, Sakshi; Bagchi, Debabrata; Rao, Ankit; Vinod, Chathakudath P.; Peter, Sebastian C.; Singh, Abhishek; Eswaramoorthy, Muthusamy (ACS Applied Materials & Interfaces, 2022)
NiFe layered double hydroxide (NiFe LDH) grown in the presence of MoS2 (rich in 1T phase) shows exceptional performance metrics for alkaline oxygen evolution reaction (OER) in this class of composites. The as-prepared NiFe LDH/MoS2 composite (abbreviated as MNF) exhibits a low overpotential (eta(10)) of 190 mV; a low Tafel slope of 31 mV dec(-1); and more importantly, a high stability in its performance manifested by the delivery of current output for 45 h. It is important to note that this could be achieved with an exceedingly low loading of 0.14 mg cm(-2). The mass activity of this composite (97 A g(-1)) is about 14 times greater than that of the conventional RuO2 (7 A g(-1) ) at eta = 200 mV. When normalized with respect to the total metal content, a mass activity of 1000 A g(-1) (eta = 300 mV) was achieved. Impedance analysis further reveals that the significant reduction in charge-transfer resistance and hence high current density (5 times greater as compared to NiFe LDH at eta = 300 mV) observed for MNF is associated with interfacial adsorption kinetics of intermediates (R-1). Significant enhancement in the intrinsic activity of MNF over LDH has been observed through normalization of current with the electrochemically active surface area. Computational studies suggest that the Ni centers in the composite act as the active sites for OER, which is well-corroborated with the observed postreaction appearance of Ni3+ species.
Keywords: Impedance; LDH-MoS2 hybrid electrocatalyst; mass activity; OER; overpotential

Influence of support textural property on CO2 to methane activity of Ni/ SiO2 catalysts - Cherevotan, Arjun; Ray, Bitan; Churipard, Sathyapal R.; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Applied Catalysis B-Environmental, 2022)
In this work, we elucidated the role of physicochemical textural properties of inert support on the catalyst ac-tivity by impregnating Ni on ordered mesoporous silica (SBA-15 and MCM-41) and non-mesoporous silica (nMPS). The catalyst Ni/SBA-15 exhibited the best CO2 conversion (83%) and product selectivity (99.9 %) followed by Ni/MCM-41 and the least by Ni/nMPS. The difference in the nature of the catalyst, degree of nanoparticle distribution and nanoparticle encapsulation by different silica support were studied by N2 adsorption-desorption and X-ray photoelectron spectroscopy (XPS) experiments. The Operando Diffused Reflec-tance Infrared Fourier Transform Spectroscopy were used to understand the variance in reaction pathway which is accredited to the textural properties of the support. The SBA-15 supported Ni catalyst followed dissociative CO pathway while MCM-41 and nMPS reacted through associative formate mechanism as major pathway. These findings provide a novel perspective on CO2 hydrogenation over Ni-silica, allowing us to tune both activity and selectivity.
Keywords: CO2 methanation; DRIFTS; Mesoporous silica support; Textural properties

Noble-metal-free heterojunction photocatalyst for selective CO2 reduction to methane upon induced strain relaxation - Das, Risov; Sarkar, Shreya; Kumar, Ritesh; Ramarao, Seethiraju D.; Cherevotan, Arjun; Jasil, Mohammed; Vinod, Chathakudath P.; Singh, Abhishek Kumar; Peter, Sebastian C. (ACS Catalysis, 2022)
Sunlight-driven CO2 hydrogenation has drawn tremendous attention. However, selective CH4 formation via CO2 photoreduction is very challenging. Herein, we report a metal oxide semiconductor heterojunction consisting of BiVO4 and WO3 as a photocatalyst for the efficient conversion of carbon dioxide (CO2) selectively to methane (105 mu mol g(-1) h(-1)) under visible light in the absence of a sacrificial agent. Wise selection of the reaction medium and the strategically tuned heterojunction upon strain relaxation suppresses the competitive hydrogen generation reaction. The detailed photophysical, photoelectrochemical, and X-ray absorption spectroscopy studies pointed to the Z-scheme mechanism of electron transfer, which favors superior electron and hole separation compared to the individual components of the composite catalyst and other well-known photocatalysts reported for CO2 reduction. The observations are further corroborated by experimental diffuse reflectance infrared Fourier transform spectroscopy and theoretical density-functional theory calculations, which reveal that the heterojunction has a lower free-energy barrier for CO2 conversion to CH4 due to the larger stabilization of the *CH2O intermediate on the strain-relaxed heterojunction surface, in comparison to the pristine BiVO4 surface. The present work provides fundamental insights for constructing high-performance heterojunction photocatalysts for the selective conversion of CO2 to desired chemicals and fuels.
Keywords: CO2 reduction; heterostructure; methane; Photocatalysis; Z-scheme

Potential- and time-dependent dynamic nature of an oxide-derived pdin nanocatalyst during electrochemical CO2 reduction - Bagchi, Debabrata; Sarkar, Shreya; Singh, Ashutosh Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (ACS Nano, 2022)
Electrochemical reduction of CO2 into valuable fuels and chemicals is a promising route of replacing fossil fuels by reducing CO2 emissions and minimizing its adverse effects on the climate. Tremendous efforts have been carried out for designing efficient catalyst materials to selectively produce the desired product in high yield from CO2 by the electrochemical process. In this work, a strategy is reported to enhance the electrochemical CO2 reduction reaction (ECO2RR) by constructing an interface between a metal-based alloy (PdIn) nanoparticle and an oxide (In2O3), which was synthesized by a facile solution method. The oxide-derived PdIn surface has shown excellent eCO(2)RR activity and enhanced CO selectivity with a Faradaic efficiency (FE) of 92.13% at -0.9 V (vs RHE). On the other hand, surface PdO formation due to charge transfer on the bare PdIn alloy reduces the CO2RR activity. With the support of in situ (EXAFS and IR) and ex situ (XPS, Raman) spectroscopic techniques, the optimum presence of the Pd-In-O interface has been identified as a crucial parameter for enhancing eCO(2)RR toward CO in a reducing atmosphere. The influence of eCO(2)RR duration is reported to affect the overall performance by switching the product selectivity from H-2 (from water reduction) to CO (from eCO(2)RR) on the oxide-derived alloy surface. This work also succeeded in the multifold enhancement of the current density by employing the gas diffusion electrode (GDE) and optimizing its process parameters in a flow cell configuration.
Keywords: CO2 reduction; Electrochemistry; heterostructure interface; in situ mechanism; nanocatalyst

Tuning the hybridization and charge polarization in metal nanoparticles dispersed over Schiff base functionalized SBA-15 enhances CO2 capture and conversion to formic acid - Cherevotan, Arjun; Ray, Bitan; Yadav, Anish; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Churipard, Sathyapal R.; Naral, Vinay; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2022)
Different Schiff base functionalized SBA-15 materials were synthesized through condensation reactions between 3-aminopropyltriethoxysilane (APTES) and different aldehydes (glutaraldehyde and butyraldehyde) over a mesoporous silica, SBA-15 (APTES-GLU/SBA-15 and APTES-BUT/SBA-15). Both static and dynamic experiments have been used for testing the CO2 capture efficiency of these materials. The hybridization of the N atom in APTES has been tuned from sp(3) to sp(2) upon condensation facilitating optimum CO2 capture in the direct synthesis of APTES-GLU/SBA-15. The undesirable oxides of nitrogen have been removed during the synthesis process to improve the CO2 capture efficiency. These materials were employed as supports for Pd-Ag and Pd-Ni bimetallic systems for the selective conversion of the captured CO2 to formic acid (FA) in 0.5 M KHCO3 solution. The Pd-Ni catalyst system exhibited enhanced CO2 to FA conversion activity compared to other heterogeneous systems, which is similar to 4 times better than that of the Pd-Ag system in this study. The X-ray absorption studies over the catalyst material confirmed that the relatively electron-deficient Ni in Pd-Ni compared to Ag in Pd-Ag favoured higher charge polarization between the metals in the Pd-Ni system enhancing the CO2 to FA conversion. The experimental observations are well supported by the DFT calculations.

Distortion-induced interfacial charge transfer at single cobalt atom secured on ordered intermetallic surface enhances pure oxygen production - Mondal, Soumi; Riyaz, Mohd; Bagchi, Debabrata; Dutta, Nilutpal; Singh, Ashutosh Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (ACS Nano, 2023)
In this work, atomic cobalt (Co) incorporation into the Pd2Ge intermetallic lattice facilitates operando generation of a thin layer of CoO over Co-substituted Pd2Ge, with Co in the CoO surface layer functioning as single metal sites. Hence the catalyst has been titled Co-1-CoO-Pd2Ge. High-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy confirm the existence of CoO, with some of the Co bonded to Ge by substitution of Pd sites in the Pd2Ge lattice. The role of the CoO layer in the oxygen evolution reaction (OER) has been verified by its selective removal using argon sputtering and conducting the OER on the etched catalyst. In situ X-ray absorption near-edge structure and extended X-ray absorption fine structure spectroscopy demonstrate that CoO gets transformed to CoOOH (Co3+) in operando condition with faster charge transfer through Pd atoms in the core Pd2Ge lattice. In situ Raman spectroscopy depicts the emergence of a CoOOH phase on applying potential and shows that the phase is stable with increasing potential and time without getting converted to CoO2. Density functional theory calculations indicate that the Pd2Ge lattice induces distortion in the CoO phase and generates unpaired spins in a nonmagnetic CoOOH system resulting in an increase in the OER activity and durability. The existence of spin density even after electrocatalysis is verified from electron paramagnetic resonance spectroscopy. We have thus successfully synthesized intermetallic supported CoO during synthesis and rigorously verified the role played by an intermetallic Pd2Ge core in enhancing charge transfer, generating spin density, improving electrochemical durability, and imparting mechanical stability to a thin CoOOH overlayer. Differential electrochemical mass spectrometry has been explored to visualize the instantaneous generation of oxygen gas during the onset of the reaction.
Keywords: DEMS; interfacial charge transfer; Intermetallic; long-termstability; operando spectroscopic techniques; Oxygen Evolution Reaction; structuraldistortion

Intrinsic charge polarization in Bi19S27Cl3 nanorods promotes selective C-C coupling reaction during photoreduction of CO2 to ethanol - Das, Kousik; Das, Risov; Riyaz, Mohd; Parui, Arko; Bagchi, Debabrata; Singh, Ashutosh Kumar; Singh, Abhishek Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (Advanced Materials, 2023)
Obtaining multi-carbon products via CO2 photoreduction is a major catalytic challenge involving multielectron-mediated C-C bond formation. Complex design of multicomponent interfaces that are exploited to achieve this chemical transformation, often leads to untraceable deleterious changes in the interfacial chemical environment affecting CO2 conversion efficiency and product selectivity. Alternatively, robust metal centers having asymmetric charge distribution can effectuate C-C coupling reaction through the stabilization of intermediates, for desired product selectivity. However, generating inherent charge distribution in a single component catalyst is a difficult material design challenge. Here, a novel photocatalyst, Bi19S27Cl3, is presented which selectively converts CO2 to a C-2 product, ethanol, in high yield under visible light irradiation. Structural analysis through transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy reveals the presence of charge polarized bismuth centers in Bi19S27Cl3. The intrinsic electric field induced by charge polarized bismuth centers renders better separation efficiency of photogenerated electron-hole pair. Furthermore, charge polarized centers yield better adsorption of CO* intermediate and accelerate the rate determining C-C coupling step through the formation of OCCOH intermediate. Formation of these intermediates is experimentally mapped by in situ Fourier-transform infrared spectroscopy and further confirmed by theoretical calculation.
Keywords: C-C coupling; charge polarization; CO2 reduction; Ethanol; Photocatalysis

Wadsworth-emmons reaction by using the fluorapatite catalyst: kinetic studies - Vishwakarma, Rakhi; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Industrial & Engineering Chemistry Research, 2023)
Wadsworth-Emmons reaction was successfully carriedout byusing the fluorapatite (FAP) catalyst. The reaction of 2-methoxybenzaldehydeand triethylphosphonoacetate using FAP afforded & alpha;,& beta;-unsaturatedester with 100% conversion and 80% selectivity. A kinetic model wasvalidated at different temperatures by Langmuir-Hinshelwood-Hougen-Watson(LHHW), and the absence of mass transfer resistance was verified bythe Weisz Prater criterion. The effect of different catalysts, temperature,catalyst loading, solvent, mole ratio, and speed of stirring was studied.The FAP catalyst was characterized by Fourier transform infrared spectroscopy,Brunauer-Emmett-Teller method, nitrogen adsorption-desorption,transmission electron microscopy, energy-dispersive X-ray spectroscopy,temperature programmed desorption (TPD-NH3), X-ray diffraction,and X-ray photoelectron spectroscopy. The FAP catalyst was found tobe stable up to three recycles with no loss in activity.

Wurtzite CuGaS2 with an in-situ-formed CuO layer photocatalyzes CO2 conversion to ethylene with high selectivity - Chakraborty, Subhajit; Das, Risov; Riyaz, Mohd; Das, Kousik; Singh, Ashutosh Kumar; Bagchi, Debabrata; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte chemie-international edition, 2023)
We present surface reconstruction-induced C-C coupling whereby CO2 is converted into ethylene. The wurtzite phase of CuGaS2. undergoes in situ surface reconstruction, leading to the formation of a thin CuO layer over the pristine catalyst, which facilitates selective conversion of CO2 to ethylene (C2H4). Upon illumination, the catalyst efficiently converts CO2 to C2H4 with 75.1 % selectivity (92.7 % selectivity in terms of R-electron) and a 20.6 mu mol g(-1) h(-1) evolution rate. Subsequent spectroscopic and microscopic studies supported by theoretical analysis revealed operando-generated Cu2+, with the assistance of existing Cu+, functioning as an anchor for the generated *CO and thereby facilitating C-C coupling. This study demonstrates strain-induced in situ surface reconstruction leading to heterojunction formation, which finetunes the oxidation state of Cu and modulates the CO2 reduction reaction pathway to selective formation of ethylene.
Keywords: C-C coupling; charge polarization; CO2 reduction; Photocatalysis

Hydrogenation of glucose to sorbitol by using nickel hydroxyapatite catalyst - Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra K.; Lakshmi Kantam, Mannepalli (Chemcatchem, 2024)
A series of nickel hydroxyapatite catalysts were synthesized by the co-precipitation method followed by calcination and reduction. These catalysts were employed for the aqueous phase hydrogenation of glucose to sorbitol. The Ni-HAP catalyst with comparatively high surface area and acid-base strength gave high sorbitol selectivity in 1 h. Ni-HAP-4 catalyst with moderate Ni (3.5 wt. %) content having smaller and highly dispersed nickel particles gives an excellent yield of sorbitol, 97 % in 1 h. The Ni-HAP-4 catalyst works well with other polar protic solvents. Different characterization techniques like XRD, TEM, SEM-EDS, BET, NH3-TPD, and CO2-TPD were employed to analyze the Ni-HAP-4 catalyst. A facile hydrogenation of glucose to sorbitol has been reported with Ni-HAP catalyst using water as a solvent. The excellent yield of sorbitol, 97 % in 1 h is possible due to the high surface area and high acid-base strength of the Ni-HAP-4 catalyst. image
Keywords: glucose; Hydrogenation; Hydroxyapatite (HAP); Nickel; Sorbitol

Photocatalytic regeneration of reactive cofactors with inP quantum dots for the continuous chemical synthesis - Chakraborty, Indra Narayan; Jain, Vanshika; Roy, Pradyut; Kumar, Pawan; Vinod, Chathakudath P.; Pillai, Pramod P. (ACS Catalysis, 2024)
The shuttling of redox-active nicotinamide cofactors between the light and dark cycles is the key to the continuous production of biomass in photosynthesis. The replication of such processes in artificial photosynthetic systems demands fast photoregeneration as well as simultaneous integration of these nicotinamide cofactors into the dark cycle. Here, we report the design of an artificial photosynthetic system for the continuous production of butanol via the constant photoregeneration and consumption of nicotinamide cofactors, powered by an indium phosphide quantum dot (InP QD) photocatalyst and alcohol dehydrogenase (ADH) enzyme, respectively. A strong electrostatic attraction between the oppositely charged InP QDs and electron mediators significantly enhanced the charge extraction and utilization processes, enabling a fast (similar to 30 min, with a turn over frequency of similar to 1333 h(-1)), quantitative (>99%), and selective photoregeneration of enzymatically active nicotinamide cofactors in the light cycle. These photoregenerated nicotinamide cofactors were further coupled in the dark cycle to trigger the ADH oxidoreductase enzyme for the production of butanol, via sequential as well as simultaneous light-dark cycles. The amount of butanol produced under simultaneous light-dark cycles was higher than the stoichiometric limit, proving the constant regeneration and consumption of nicotinamide cofactors in light and dark cycles, respectively. Thus, a proper design and integration of the InP QD-based photocatalytic cycle with the enzymatic cycle led to the effective electron shuttling between light and dark cycles, as seen in photosynthesis.
Keywords: artificial photosynthesis; biologicalcofactors; charge transfer; indiumphosphide; Photocatalysis; quantum dots

Unraveling the cooperative mechanisms in ultralow copper-loaded WC@NGC for enhanced CO2 electroreduction to acetic acid - Bagchi, Debabrata; Riyaz, Mohd; Raj, Jithu; Roy, Soumyabrata; Singh, Ashutosh Kumar; Cherevotan, Arjun; Vinod, Chathakudath P.; Peter, Sebastian C. (Chemistry of Materials, 2024)
Electrochemical CO2 reduction reaction (eCO(2)RR) has been explored on tungsten carbide (WC) nanoparticles embedded on N-doped graphitic carbon (NGC), demonstrating excellent activity toward the formation of acetic acid at an extremely lower potential. The activity has been further enhanced by loading ultralow copper sites into the catalyst system, exhibiting 80.02% Faradaic efficiency (FE) toward acetic acid at an applied potential of -0.3 V (vs RHE). Potential-dependent in situ infrared (IR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, ex situ extended X-ray absorption fine structure (EXAFS) studies, and computational analysis confirm that synergy between uniformly dispersed Cu atoms and WC lattice plays a crucial role in the formation of acetic acid with high FE at a lower potential. It has been observed that the W atom of WC strongly chemisorbs CO2 with a significant change in the C-O bond length and the O-C-O bond angle, in contrast to weaker adsorption on Cu-based catalyst surfaces. The presence of a Cu site enhances the adsorption of CO2, thereby increasing the possibility of C-C coupling kinetically. Most importantly, hydrogen evolution predominates on the catalyst's surface at higher applied potentials (-0.5 to -1.1 V vs RHE), elucidating the mechanism underlying enhanced charge transfer between copper and WC, a phenomenon ascertained through in situ IR spectroscopy and ex situ XPS analysis

Dopant and exfoliation induced simultaneous modification of charge density and C―C coupling sites for efficient CO2 photoreduction to ethylene - Das, Kousik; Chakraborty, Subhajit; Kediya, Siddhi; Singh, Ashutosh Kumar; Das, Risov; Mondal, Soumi; Riyaz, Mohd; Goud, Devender; Dutta, Nilutpal; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte Chemie-International Edition, 2025)
The photochemical conversion of CO2 into C2+ products has emerged as an attractive method for synthesizing valuable chemicals and fuels using abundant solar energy. However, the challenge lies in enhancing the efficiency and selectivity of C2+ product formation. In this study, we employed a heteroatom doping strategy to optimize the photocatalytic parameters and achieve excellent efficiency and selectivity in the photocatalytic CO2 reduction to C2+ product formation. Our experimental analysis revealed that the local electronic structure of the catalyst, modified by In-doping, enables enhanced efficiency. Additionally, the incorporation of Cu facilitates the coupling of C1 intermediates, resulting in excellent selectivity towards C2+ products. The CO2 reduction performance is further enhanced through exfoliation, which increases the exposure of active sites and extends the charge carrier lifetime by reducing the charge diffusion length. We report that the rate of formation of C2H4 reached 54.3 mu molh(-1)g(-1) with an outstanding selectivity of 91% over the exfoliated CuIn-doped AgBiP2S6 catalyst. By elucidating the role of heteroatom doping and exfoliation in enhancing both the efficiency and selectivity of C2+ product formation, our study contributes to advancing the development of sustainable and efficient photocatalytic CO2 conversion technologies.
Keywords: C & horbar; C coupling; CO2 reduction; Doping; Exfoliation; Photocatalysis

Metal deficiency tuned charge transfer in intermetallic Ni2-xSn (x =0.37-0.65) enhances selective conversion of furfural to furfuryl alcohol towards the theoretical limit - Cherevotan, Arjun; Singh, Ashutosh Kumar; Yadav, Anish; Maligal-Ganesh, Raghu V.; Raj, Jithu; Pulparambil, Anu; Goud, Devender; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2025)
Heterogeneous catalysis facilitated by intermetallic nanoparticles has recently been the subject of increased scrutiny, given the enhanced selectivity and stability they bestow on many chemical reactions compared to their monometallic components. This paper explores a series of Ni-Sn (Ni2-xSn, where x = 0.65, 0.5, 0.37) intermetallic compounds supported on a high-surface-area support, SBA-15, as catalysts for the selective hydrogenation of furfural to furfuryl alcohol. Rietveld refinements of the X-ray diffraction data show catalysts with mixed intermetallic phases that assist in the catalysis. At the same time, X-ray photoelectron spectroscopy (XPS) studies and X-ray absorption studies indicate the role played by charge transfer from Sn to Ni for the catalysis. Selectivity to the desired furfuryl alcohol in all the intermetallic samples was high (>97%), but Ni1.35Sn had a relatively lower conversion than the other intermetallic compounds.

Synthesis of 5-hydroxymethylfurfural from glucose using a tert-butoxyapatite catalyst - Kulkarni, Hemant S.; Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (DALTON TRANSACTIONS, 2025)
In this study, 5-hydroxymethylfurfural (5-HMF) was obtained from glucose using tert-butoxyapatite, a heterogeneous catalyst. The tert-butoxyapatite catalyst was prepared and characterized by several techniques, such as XRD, SEM, TEM, EDS, elemental mapping HR-TEM, N2-adsorption/desorption, XPS, and FT-IR. Several parameters were studied, such as temperature, catalyst loading, and glucose concentration. The tert-butoxyapatite catalyst having both acidic and basic sites gave a maximum glucose conversion of 87% with a 48% yield of HMF at 160 degrees C using 20 wt% catalyst in 12 h. Reusability studies of the catalyst are also presented.

Synthesis of glycolic acid from glyoxal by using hydrotalcite catalyst and kinetic studies - Pandya, Harmitkumar N.; Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (ChemCatChem, 2025)
In this work, Mg-Al hydrotalcite catalysts with different molar ratios were prepared using the co-precipitation method for the synthesis of glycolic acid (GA) from glyoxal. Various reaction parameters such as catalyst molar ratio, time, temperature, catalyst loading, and catalyst poisoning were studied and optimized for better conversion of glyoxal selectively to glycolic acid. Hydrotalcite catalyst with a 2:1 molar ratio of Mg: Al gives 98% conversion of glyoxal with 96% selectivity of glycolic acid at 100 degrees C temperature, 40% catalyst loading, and water as solvent in 8 h. Different characterization methods were used such as XRD, XPS, SEM-EDX, nitrogen adsorption desorption, and CO2-TPD for hydrotalcite catalyst. A kinetic study was also performed to observe the reaction order and activation energy required for the reaction.
Keywords: Glycolic acid; Glyoxal; hydrotalcite; kinetics

Towards improved activity and stability in RWGS reaction: Dispersed copper in mesoporous alumina matrix as a strategy for enhanced performance - Saju, Simi; Rajendran, Sivaraj; Oztas, Ulviye; Ruiz, Sergio Carrasco; Reina, Tomas Ramirez; Ghosh, Biplab; Sree, Sreeprasanth Pulinthanathu; Meena, Raghavendra; Li, Guanna; Bobadilla, Luis F.; Vinod, Chathakudath P.; Mathew, Thomas; et al. (Chemical Engineering Journal, 2025)
The development of highly performing Cu-based catalysts with high dispersion of Cu species in nanocrystalline form on a suitable oxide support is significant in reverse water gas shift (RWGS) reaction. We report a simple and robust one-pot sol-gel synthesis of mesoporous Al10-xCuxOy (m gamma-Al10-xCux-SG) catalysts with Cu species in a highly dispersed nanocrystalline form in the gamma-Al2O3 matrix and its high catalytic performance in RWGS reaction. The lack of long range structural order of copper species in m gamma-Al10-xCux-SG catalysts evidenced from Cu-K edge extended X-ray absorption fine structure (EXAFS) studies illustrates the fine distribution of copper species in mesoporous gamma-Al2O3 lattice. Activity study revealed that m gamma-Al10-xCux-SG catalysts showed significantly high CO2 conversion to CO and excellent catalytic stability compared to gamma-Al10-xCux-I prepared by conventional impregnation method. Mesoporous Al9Cu1 (m gamma-Al9Cu1) displayed a CO2 conversion of 45 % at 500 degrees C, which is about 2.8 times higher activity than conventional gamma-Al9Cu1-I catalyst with almost same Cu loading as that of m gamma-Al9Cu1 catalyst. Stability study at 500 degrees C over a period of 50 h revealed that m gamma-Al10-xCux-SG catalysts at low Cu loading (m gamma-Al9.9Cu0.1) showed excellent catalytic stability. The strong copper-alumina interaction in m gamma-Al10-xCux-SG catalysts with enhanced number of active sites at the copper-alumina interface as evidenced from field emission scanning electron microscope (FESEM), high-resolution transmission electron microscope (HRTEM), H2-temperature programmed reduction (H2-TPR), X-ray photoelectron spectroscopy (XPS), electrochemical characterization, and Cu-K edge EXAFS analysis enhances the activity and stability of the catalyst. Density functional theory (DFT) studies and the Operando DRIFTS-MS analysis of RWGS over m gamma-Al9Cu1 catalyst revealed that the mechanism of RWGS reaction to CO formation on m gamma-Al10-xCux-SG catalysts is preceded through the formation of a hydroxycarbonyl (OCOH) intermediate. The present synthesis strategy provides an opportunity for producing Cu-based catalysts with further enhanced activity and stability in RWGS reaction by suitable modification of the catalyst.

Ultra-small Pd nanoparticles on SBA-15: an efficient catalyst for one-pot reductive alkylation of nitrobenzene with size-dependent activity - Soni, Yogita; Philip, Milda C.; Vinod, Chathakudath P. (Topics in Catalysis, 2025)
One-pot reductive alkylation of nitrobenzene with alcohol is an important organic synthesis reaction to form 2 degrees amines. In the present work, we have demonstrated that Pd/SBA-15 can be an effective catalytic system for this reaction. We have designed ultra-small Pd nanoparticles supported on SBA-15 for the synthesis of secondary amine, N-ethylaniline, through one-pot reductive alkylation of nitrobenzene with ethanol under ambient conditions. Ethanol functions both as the alkylating agent and the solvent in this process. The reaction is driven by the simultaneous hydrogenation of nitrobenzene to aniline, dehydrogenation of ethanol to aldehyde, and condensation of aniline and acetaldehyde to form N-ethylaniline. The size of the Pd nanoparticles plays a decisive role in the product selectivity. The undercoordinated sites present on ultra-small Pd NPs can facilitate ethanol dehydrogenation to acetaldehyde, thereby enhancing the selectivity towards N-ethylaniline compared to larger Pd nanoparticles. We have also studied the effect of different mesoporous supports such as SBA-15, MCM-41, and KIT-6 on the N-ethylaniline selectivity and found that SBA-15 was most selective. We have demonstrated that by carefully designing the catalyst such as controlling the Pd NPs size to obtain the maximum quantity of undercoordinated sites and choosing suitable support, the aliphatic alcohols can also be used for reductive alkylation of nitrobenzene in one-pot with optimum yields of N-alkylaniline.
Keywords: KIT-6; MCM-41; Modified deposition precipitation; nitrobenzene; Pd nanoparticles; Reductive alkylation; SBA-15; secondary amines; Undercoordinated Pd sites

W/HAP catalyzed terpenic alcohols oxidation: kinetic studies - Poman, Aishwarya; Kamble, Paresh; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Reaction Chemistry & Engineering, 2025)
The selective oxidation of natural alcohols into carbonyl derivatives is a pivotal transformation in synthetic organic chemistry and industrial applications. This study focuses on the oxidation of borneol, a bicyclic secondary terpenic alcohol, into camphor using a tungsten-exchanged hydroxyapatite (W/HAP) catalyst and hydrogen peroxide as a green oxidant. Hydroxyapatite was synthesized via co-precipitation and functionalized with sodium tungstate to create the W/HAP catalyst, which was characterized using techniques such as SEM, EDS, TPD, XPS, and N2 adsorption-desorption to evaluate its surface morphology, porosity, and chemical composition. Oxidation reactions were conducted under optimized conditions, employing dimethylacetamide (DMA) as a solvent to achieve maximum conversion and selectivity. The W/HAP catalyst demonstrated superior performance, achieving nearly 99% conversion of borneol with 100% selectivity for camphor. Reaction parameters, including temperature, reactant stoichiometry, solvent choice, and catalyst loading, were systematically investigated. Higher reaction temperatures and oxidant concentrations favoured rapid conversion while maintaining high selectivity. Solvent effects revealed that DMA stabilized peroxo-tungstate intermediates, enhancing reaction efficiency compared to other solvents. Kinetic studies confirmed a first-order reaction mechanism with respect to borneol, and the activation energy was determined to be 44.23 kJ mol-1, highlighting the catalytic efficiency of W/HAP. Reusability tests confirmed the stability of the W/HAP catalyst over multiple cycles with minimal tungsten leaching. The methodology was extended to other terpenic alcohols, with varying degrees of success, emphasizing the substrate-specific activity of the catalyst. This work underscores the potential of tungsten-based heterogeneous catalysts in sustainable alcohol oxidation and highlights the industrial relevance of camphor synthesis as a renewable and eco-friendly approach to produce fine chemicals, fragrances, and pharmaceuticals.